Health Risks and Benefits Among Surfers After Exposure to Seawater in Monterey Bay, Santa Cruz County, California, United States - O’Halloran, Chris; Silver, Mary (Frontiers in Marine Science, 2021)
We investigated the health risks and benefits among surfers in Monterey Bay, Santa Cruz County, California, United States after seawater exposure. A total of 47 surfers enrolled and completed an online survey on the effect of the ocean environment on their well-being, physical and mental health, and provided their perspectives on ocean conservation. The majority of the surfers were white males, with a median age of 40 years, and a mean of 21 years surfing experience. Most of the participants spent over 5 h/week in the ocean. The most common health problems reported were adverse effects due to red tide exposure, surfer’s ear, back and neck problems, and allergies. A total of 41% reported upper respiratory symptoms, and 8% of the participants reported gastrointestinal symptoms. All participants reported that the ocean benefited their emotional health, and 45/47 (>96%) reported that the ocean increased their life satisfaction, happiness, and decreased their stress level. All participants reported being engaged in ocean stewardship. This study suggests surfers were significantly more likely to report upper respiratory symptoms when they had experienced adverse health effects while surfing during a “red tide” and during a bloom of the microscopic, single-celled phytoplankter, Akashiwo sanguinea.